Features, Causes and Prevention of Toxic Anterior Segment Syndrome (TASS) - An Outbreak Investigation - Shoaib, Khawaja Khalid (Pakistan Journal of Ophthalmology, 2018)
Purpose: To analyze features, causes and preventive measures for toxic anterior segment syndrome (TASS) cases, occurring after coaxial phacoemulsification (phaco). Material and Methods: TASS occurring after uneventful coaxial phaco during May/June 2008 in eye department, Combined Military Hospital Kharian, were analyzed retrospectively in this case series. Clinical features, response to treatment and possible causes were checked during the outbreak (including intracamerally given drugs, irrigating solutions, intraocular lenses and washing/ sterilization techniques for instruments) and measures taken to prevent further cases. Follow up continued till Feb 2009. Results: Nineteen (14.8%) out of 128 phaco cases developed TASS. Out of these nineteen cases, nine (47%) were males and ten (53%) were females. Age ranged from twenty eight years to seventy one years (mean 57 ± 9.7). Follow up ranged from one month to seven months (mean 2.2 ± 2.1). Post operatively, one patient had nausea and vomiting six hours after the operation. On first post operative day, there was corneal edema, anterior chamber inflammation, pupil dilatation, and pigment dusting on the corneal endothelium / anterior surface of intraocular lens in all (100%) cases. At last visit, eight cases (42 %) had corneal haze, seven (37%) had iris atrophy and two (11%) had dilated pupil. Corrected visual acuity became 6/6 in nine cases (47%), rest ranged from 6/6P to hand movement. Different steps were taken to stop TASS and no case occurred in next seven months from July 2008 onwards. Conclusion: TASS can result in corneal haze or iris depigmentation / atrophy. Even prompt and energetic treatment may leave significant visual morbidity. The exact cause could not be established in this series of cases however more vigilance resulted in cessation of such cases.